2007
DOI: 10.1074/jbc.m611761200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Role of Extracellular Loop Cysteine Residues of the Epithelial Na+ Channel in Na+ Self-inhibition

Abstract: The epithelial Na ؉ channel (ENaC) is typically formed by three homologous subunits (␣, ␤, and ␥) that possess a characteristic large extracellular loop (ECL) containing 16 conserved cysteine (Cys) residues. We investigated the functional role of these Cys residues in Na ؉ self-inhibition, an allosteric inhibition of ENaC activity by extracellular Na ؉ . All 16 Cys residues within ␣ and ␥ ECLs and selected ␤ ECL Cys residues were individually mutated to alanine or serine residues. The Na ؉ self-inhibition resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
57
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 45 publications
5
57
0
Order By: Relevance
“…Given the similarities in amino acid sequences and biophysical properties among ASIC and other members of ENaC/degenerin family, it is very likely that ENaC subunits adopt a similar overall tertiary structure, although considerable differences likely exist within local structures, particularly for poorly conserved regions that likely contribute to differences in the biophysical properties of ASIC and ENaC. Additional evidence supporting the notion that ECDs of ASIC and ENaC share a similar overall structure is that the disulfide bridges proposed for the ECD of ␣ ENaC, based on mutational analyses and chemical modifications, match the disulfide bonds within the cASIC1 structure (9,14).…”
mentioning
confidence: 72%
See 3 more Smart Citations
“…Given the similarities in amino acid sequences and biophysical properties among ASIC and other members of ENaC/degenerin family, it is very likely that ENaC subunits adopt a similar overall tertiary structure, although considerable differences likely exist within local structures, particularly for poorly conserved regions that likely contribute to differences in the biophysical properties of ASIC and ENaC. Additional evidence supporting the notion that ECDs of ASIC and ENaC share a similar overall structure is that the disulfide bridges proposed for the ECD of ␣ ENaC, based on mutational analyses and chemical modifications, match the disulfide bonds within the cASIC1 structure (9,14).…”
mentioning
confidence: 72%
“…We recently reported that point mutations at multiple ␣ and ␥ ECD Cys residues blunted Na ϩ self-inhibition, and certain double or triple mutations rendered ENaC insensitive to high concentration of extracellular Na ϩ . These results suggest that multiple Cys residues are required to establish the proper tertiary structure permitting this allosteric regulation (9). In addition, the N-terminal portion of ECD contains ␥His 239 , a previously identified residue critical for Na ϩ self-inhibition, as well as defined protease cleavage sites (4, 10 -12).…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…The thumb domains of the ENaC/degenerin family of ion channels are poorly conserved yet share two important features: two predicted helices and 10 absolutely conserved Cys that form a five-disulfide bond ladder (12,15). These hallmark features of ENaC/degenerin channels suggest that the antiparallel arrangement of the two thumb helices in ASIC1 is widely conserved.…”
Section: Discussionmentioning
confidence: 99%